441 Policy action to promote the development of child maltreatment prevention action plans in Europe. (1st September 2016) - Sethi, Dinesh; Crispino, Vittoria
Abstract : Background: Child maltreatment is common in globally and in the European Region. In the European facts and the Global status report on violence prevention, 78% of the countries participating reported that they had developed action plans to prevent child maltreatment. Investing in Children: the European Child Maltreatment Prevention Action Plan 2015–2020 adopted by Member States has an aspirational target to reduce child maltreatment by 20% by 2020. To determine whether these plans are likely to result in programme implementation, a content analysis was undertaken. Methods: National data coordinators from the 41 countries in the WHO European Region that took part in the global survey were contacted to request copies of national action plans (NAPs). Internet searches were also conducted on the official government web sites. On this basis, 35 NAPs were identified, of which four were sub-national. A content analysis was conducted using an established methodological framework (Schopper et al). Results: Almost all NAPs (97%) described multisectoral engagement. Whereas all NAPs had clearly stated objectives, in only one was there a quantified target. All NAPs had achieved government approval; however only 43% had a clearly stated budget for implementation and 66% had a clearly stated lead agency for coordinating the actions of the different actors. Whereas 94% had clearly outlined interventions and activities aimed at achieving the corresponding objectives, all focused on child protection interventions (such as detection, helplines), and fewer had an emaphsis on primary prevention activities such as home vsiitng and prenting support. Countries with NAPs were more likely to have primary prevention interventions than those without. Conclusions: This analysis shows that progress is being made in developing action plans for child maltreatment prevention, but inadequate attention is being given to preventive interventions and most of the focus is on child protection. Governance mechanisms need to be strengthened to ensure more concerted national actions. It is proposed that one way forward would be the development of more NAPs with a clearly defined lead agency, budget and quantified targets. These findings will be discussed in the light of policy success stores from other areas such as road safety.